Kehidupan Keluarga Pelaku Wisata Digital: Studi Tentang Pembagian Peran Gender di Bira: Penelitian - Fajri Akbar Putra; Sri Nurhalisah; Serli Muliani; A. Octamaya Tenri Awaru; Liza Dwi Eftiza Khairunniza (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study examines gender role division within families of digital tourism actors in Bira and the factors influencing it. Bira, a leading tourist village in Bulukumba Regency, is undergoing a transformation into a digital village with technology applied in marketing, reservations, and payment systems. The study employed a descriptive qualitative approach using purposive sampling of eight informants directly involved in family-based digital tourism businesses. Data were collected through in-depth interviews, participatory observation, and document review, and analyzed using Miles & Huberman’s interactive model. Data validity was ensured through source and technique triangulation.The findings show that gender roles in these families are dynamic, flexible, and adaptive. Women perform dual roles, managing domestic responsibilities while actively participating in digital tourism business operations and strategic family decision-making. Men act as supporters when circumstances allow, creating a complementary and collaborative gender relationship. Factors influencing role division include mutual agreement, family economic conditions, minimal cultural constraints, and the use of digital technology. These findings highlight that tourism digitalization facilitates the transformation of gender roles and fosters inclusive and adaptive gender relations within digital tourism families.